Polysaccharides From the Aerial Parts of Tetrastigma Hemsleyanum Diels et Gilg Induce Bidirectional Immunity and Ameliorate LPS-Induced Acute Respiratory Distress Syndrome in Mice - Lu, Jingjing; Zhu, Bingqi; Zhou, Fangmei; Ding, Xinghong; Qian, Chaodong; Ding, Zhishan; Ye, Xiaoqing (Frontiers in Pharmacology, 2022)
Tetrastigma hemsleyanum Diels et Gilg (Sanyeqing, SYQ) has traditionally been used to treat inflammation, high fever and improve immune function of patients. Polysaccharides have been proved to be one of the important components of SYQ. Previous studies have confirmed the antipyretic and antitumor effects of polysaccharides from SYQ (SYQP), and clarified that SYQP could enhance immunity through TLR4 signalling pathway. However, there were more possibilities for the mechanism by which SYQP exerted immunomodulatory effects and the role of SYQP in acute respiratory distress syndrome (ARDS) is elusive. The purpose of this study was further to explain the bidirectional modulation of immunity mechanism of SYQP in vitro and its effect in LPS-induced ARDS in vivo. Experimental results showed that SYQP significantly stimulated gene expressions of TLR1, TLR2 and TLR6 and secretion of cytokines in RAW264.7 cells. Individual or combined application of TLR2 antagonist C29 and TLR4 antagonist TAK-242 could reduce SYQP-mediated stimulation of cytokine secretion in RAW264.7 cells and mouse peritoneal macrophages (MPMs) to varying degrees. On the other hand, SYQP markedly inhibited the expression levels of inflammatory cytokines, NO, iNOS and COX-2 in LPS-treatment RAW264.7 cells. Moreover, in vivo results indicated that SYQP significantly reduced LPS-induced damage in ARDS mice through alleviating LPS-induced pulmonary morphological damage, inhibiting myeloperoxidase (MPO) expression levels, ameliorating the inflammatory cells in bronchoalveolar lavage fluid (BALF) and improving hematological status. Meanwhile, SYQP evidently reduced IL-6, TNF-α and IFN-γ secretion, the overexpression levels of TLR2 and TLR4, as well as the phosphorylation of NF-κB p65. In addition, SYQP reduced the phosphorylation of JAK2 and STAT1 and the overexpression of NLRP3, caspase-1, caspase-3 and caspase-8 in lung tissues of ARDS mice. In summary, our study confirmed that SYQP induced bidirectional immunity and ameliorated LPS-induced acute respiratory distress syndrome in mice through TLR2/TLR4-NF-κB, NLRP3/caspase and JAK/STAT signaling pathways, which provided a theoretical basis for further use of SYQP.